2012
DOI: 10.1186/1477-7517-9-14
|View full text |Cite
|
Sign up to set email alerts
|

Integrated programs for mothers with substance abuse issues: A systematic review of studies reporting on parenting outcomes

Abstract: BackgroundIntegrated treatment programs (those that include on-site pregnancy-, parenting-, or child-related services with addiction services) were developed to break the intergenerational cycle of addiction, dysfunctional parenting, and poor outcomes for mothers and children, yet there has been no systematic review of studies of parenting outcomes.ObjectivesAs part of larger systematic review to examine the effectiveness of integrated programs for mothers with substance abuse issues, we performed a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 38 publications
3
94
0
7
Order By: Relevance
“…Clearly, understanding the factors that could foster optimal outcomes for integrated interventions for parents' substance misuse and their parenting is complex (21), particularly when statistics suggested that 60-75% of mothers who entered drug treatment left before their treatment was completed (32). With relevance to the current review, however, Niccols et al (33) noted that parenting interventions focusing on parentchild attachment may be more effective than those focusing on skill development when it comes to fostering parenting improvements for parents who are substance-involved.…”
Section: Neurobiology Of Parenting and Substance Usementioning
confidence: 93%
See 1 more Smart Citation
“…Clearly, understanding the factors that could foster optimal outcomes for integrated interventions for parents' substance misuse and their parenting is complex (21), particularly when statistics suggested that 60-75% of mothers who entered drug treatment left before their treatment was completed (32). With relevance to the current review, however, Niccols et al (33) noted that parenting interventions focusing on parentchild attachment may be more effective than those focusing on skill development when it comes to fostering parenting improvements for parents who are substance-involved.…”
Section: Neurobiology Of Parenting and Substance Usementioning
confidence: 93%
“…In an effort to combat these barriers, there is an emerging consensus that parenting interventions should involve significant community advocacy (34) and should be integrated into programs that already serve substance-involved individuals of childbearing age (33). For example, more research on interventions that can be embedded into residential treatment programs, jails, and prisons is needed.…”
Section: Neurobiology Of Parenting and Substance Usementioning
confidence: 99%
“…63,[137][138][139] Further investigation is needed, particularly into how sexual and reproductive health services and parenting skills-building can be integrated into substance use treatment programmes and other health interventions serving people who use drugs. [140][141][142] High rates of abortion have been reported among women who use drugs, some of whom are also sex workers, however, reduction in abortion-related risks and integration of family planning and post-abortion care in this population has not adequately been documented. [143][144][145] Fertility-related assessments prior to pregnancy in this population are limited, although studies focused on women living with HIV in Canada, including women who use drugs, suggested that drug use did not affect fertility intentions.…”
Section: Women Who Use Drugsmentioning
confidence: 99%
“…Conversely, improvements in the living environment and wellbeing of CSAP can positively affect recovery of parents in treatment (Lander, Howsare, & Byrne, 2013). Due to this interplay, paying attention to parenthood and parenting issues during treatment may not only contribute to parents' recovery from substance abuse but may also prevent mental health disorders in a new generation (Niccols et al, 2012).…”
mentioning
confidence: 99%
“…Possibly due to the above-mentioned difficulties with implementing routine assessments of client's children and family situations, collection of data on the mental health of CSAP at the point when their parents receive treatment has been limited (Niccols et al, 2012;Oliveros & Kaufman, 2007;Reedtz, Lauritzen, & Van Doesum, 2012). More research on this subject is needed for two reasons.…”
mentioning
confidence: 99%